ANALISIS KONFLIK BATIN DAN PERWATAKAN AMBO ULENG DALAM NOVEL RINDU KARYA TERE LIYE ( KAJIAN PSIKOLOGI SASTRA) - Dayang Suhana; Susilawati, Ahmad Rathomi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This study aims to determine the factors of inner conflict and also character and the implications of learning Indonesian related to inner conflict and also character in the novel Rindu by Tere Liye. This study uses a qualitative approach with a type of library study research. The data collection technique used is the document, then the data analysis technique used in this study is the content analysis technique (content analysis) the subject for general content analysis is "Books, documents, and creative results while the technique of checking the validity of the researcher's data uses observation techniques, reference adequacy, and colleagues. The results of the study concluded that: 1.   The Inner Conflict experienced by Ambo Uleng in the Novel Rindu by Tere Liye is divided into two, namely internal and external conflicts, the forms of inner conflict are depression, and anger. 2.  The character of Ambo Uleng in the novel Rindu by Tere Liye is to have a protagonist character and is divided into round characters. The implications of the conflict in learning Indonesian related to inner conflict and also character in the novel Rindu Karya Tere Liye are continuous implications in learning Indonesian, through the analysis of inner conflict students can improve their emotional skills, and the characterization in the novel Rindu Karya Tere Liye can also enrich students' understanding of culture and history